Prenatal gunshot wound, a rare cause of maternal and fetus trauma, a case report - Molina, GA; Aguayo, WG; Cevallos, JM; Gálvez, PF; Calispa, JF; Arroyo, KA; Guzmán, LJ; Cobo, MM; Gutierrez, BM; Toapanta, RT; Briceño, MM (Elsevier, 2019)
Background: Gunshot wounds in pregnant women, although rare, represent an important cause of fetal and maternal mortality. Understanding the mechanism of injury is essential to identify the possible injuries and to adequately manage the complexity of these emergency scenarios.